Management of Residual Neuromuscular Blockade Recovery: Age-Old Problem with a New Solution - Michael S. Green; Archana Gundigi Venkatesh; Ranjani Venkataramani (Case Reports in Anesthesiology)
Neostigmine has been traditionally used as the agent of choice to reverse Neuromuscular Blockade (NMB) after muscle paralysis during general anesthesia. However, the use of neostigmine has not been without untoward events. Sugammadex is a novel drug that selectively binds to aminosteroid nondepolarizing muscle relaxants and reverses even a deep level of NMB. Controversy exists regarding the optimal dose of sugammadex that is effective in reversing the NMB after the incomplete reversal with neostigmine and glycopyrrolate. We discuss a case where sugammadex reduced the time of the recovery from NMB in a patient who had incomplete antagonisms following adequate treatment with neostigmine, aiding timely extubation without persistent residual NMB, and hence prevented the requirement of postoperative ventilation and the improvement in patient care. More randomized control studies are needed in order to conclude the appropriate dose of sugammadex in cases of incomplete reversal.